Improvement of investment activity of enterprises - Smolinska, Sofia; Yasinovska, Iryna (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2018)
The article substantiates the main ways of activating investment activity of enterprises. The ways of formation of investment resources of enterprises are presented. The estimation of state regulation of investment activity is given. It is determined that state regulation of investment activity of enterprises should be based on three groups of methods: economic, organizational and legal. The peculiarities of formation of investment policy at enterprises are explained. The main methods of financing investment projects are described. The emphasis is placed on project financing as one of the most important types of financing of investment activity of enterprises.
Keywords: state regulation; financial resources; enterprises; financing; investment activity; activation